Fernández Cifuentes, Luis. 1955: inventario y examen de disidencias. Zaragoza: Prensas Universitarias, 2023. 516 pp. (ISBN: 978-84-1340-513-1) (Rilce. Revista de Filología Hispánica, 2024)
Book Review